Preparation and properties of antistatic high-strength aramid III/MWCNTs-OH fibers - Zhang, Dingyi; Yu, Wenhe; Ni, Yalin; Hao, Xiangyang; Lu, Fenghao; Xu, Haijia (Frontiers in Materials, 2023)
Composite fibers made from aramid III and hydroxylated multiwalled carbon nanotubes (MWCNTs-OH) combine the excellent mechanical and electrical properties of both components, resulting in strong antistatic performance. However, it is of paramount importance to ensure the homogeneous dispersion of multi-walled carbon nanotubes functionalized with hydroxyl groups (MWCNTs-OH) within the aramid III spinning solution and optimize the compatibility between the two constituents to augment the overall performance of the composite fibers. To this end, this investigation successfully accomplished the dispersion of MWCNTs-OH in the spinning solution and probed the dispersion mechanism using molecular dynamics simulations. Moreover, composite fibers, comprising 2.4 weight percent MWCNTs-OH, were initially fabricated using the wet spinning method.These fibers displayed a uniform texture and a tensile strength of 1.210 GPa, signifying a noteworthy enhancement of 113.25% in comparison to the strength prior to modification.With respect to thermal behavior, the fibers exhibited a mass reduction of 21.24% within the temperature range of 0 to 538 °C. In the temperature interval from 538 to 800 °C, the mass loss diminished to 10.31%, representing a substantial 71.03% reduction when compared to the unmodified state. Remarkably, even when subjected to temperatures exceeding 800 °C, the composite fibers retained a residual mass of 68.45%, indicating a notable 61.17% increase from their initial condition. In terms of electrical properties, the fibers exhibited a specific resistance (ρ) of 3.330 × 10 9 Ω•cm, demonstrating effective antistatic behavior. In summary, the antistatic composite fibers studied in this paper can effectively mitigate the hazards of static electricity in various applications, including military protection and engineering equipment in both military and civilian fields.